ORNAMENTAL PLANTS OF CHECHNYA AND ITS ADJACENT AREAS - Musa A. Taysumov; Mukhudin U. Umarov; Marzhan A.-M. Astamirova; Aminat S. Abdurzakova; Raisa S. Magomadova; Satsiat A. Israilova; Birlant A. Khasueva; Kheda L. Khalidova (Юг России: экология, развитие, 2018)
Abstract. The aim of the research is to summarize the scattered information about the types of decorative flora of the Chechen Republic and adjacent territories; to identify highly resistant ornamental plants for cities and settlements of the North Caucasus and other territories of Russia. Discussion. Currently, in a variety of botanical gardens of the North Caucasus grows a large number of decorative plant species, widely used in green construction. However, not all species posses the quality to sufficient resist unfavorable conditions of the changed abiotic and biotic environment. Among the studied, the most valuable and promising for widespread introduction are the species of more than 122 taxa, the decorative effect of which is preserved throughout the year with no signs of aging. Many examples of the targeted use of herbs, tree species, lianas, bulbous plants were cited in the research. We give a large list of Caucasian species for growing on lawns, flowerbeds, flower gardens, alpine and stony mountains, roadsides and parks, urban parks, squares and alleys as a type of gardening. Their decorative properties, vitality, durability, life form and other bio-ecological features, attitude to abiotic factors (soil conditions, illumination, temperature, soil and atmospheric humidification conditions, etc.) were taken into account. Conclusion. We give a large list of ornamental species and various planting techniques of specific species are introduced in conditions of Chechnya and its adjacent territories as well as the methods of implementing in the landscaping practice in other (middle and northern) regions of Russia.